The impact of the lock and key strategy on the achievement of fifth graders in Arabic grammar and the attitude towards it (Journal of the College of Basic Education, 2023)
The current research aims to identify the impact of the lock and key strategy on the achievement of fifth grade students in Arabic grammar and the trend towards it. The research sample consisted of (71) students from the fifth grade of primary school at Zuhair bin Al-Qain School of the Baghdad Directorate of Education, Al-Karkh, for the academic year (2022-2023), chosen randomly to implement the experiment, where Division (B) represented the experimental group with (35) students. Division (C) represented the control group with (36) students.The researcher rewarded the two research groups (experimental and control) in the following variables: (the chronological age of the students calculated in months, the educational attainment of the fathers, the academic achievement of the mothers, and grades of the Arabic language subject for the previous academic year). And the researcher prepared the research tool (the achievement test), as it consisted in its final form of (30) objective items) and the trend scale, as it consisted in its final form of (30) items, which were verified for their validity and reliability.After implementing the experiment over a period of (12) weeks, the researcher applied the achievement test and the trend scale and using the statistical bag (SPSS-28), the results of the current research showed (the superiority of the students of the experimental group who study Arabic grammar according to the lock and key strategy over the students of the control group who studied the subject same in the usual way in the achievement test and attitude scale